Associations among MHC genes, latitude, and avian malaria infections in the rufous‐collared sparrow (Zonotrichia capensis) - Juan Rivero de Aguilar; Omar Barroso; Elisa Bonaccorso; Hector Cadena; Lucas Hussing; Josefina Jorquera; Javier Martinez; Josué Martínez‐de la Puente; Alfonso Marzal; Fabiola León Miranda; Santiago Merino; Nubia E. Matta; et al. (Ecology and Evolution, 2024)
Abstract The major histocompatibility complex (MHC) is a genetic region in jawed vertebrates that contains key genes involved in the immune response. Associations between the MHC and avian malaria infections in wild birds have been observed and mainly explored in the Northern Hemisphere, while a general lack of information remains in the Southern Hemisphere. Here, we investigated the associations between the MHC genes and infections with Plasmodium and Haemoproteus blood parasites along a latitudinal gradient in South America. We sampled 93 rufous‐collared sparrows (Zonotrichia capensis) individuals from four countries, Colombia, Ecuador, Peru, and Chile, and estimated MHC‐I and MHC‐II allele diversity. We detected between 1–4 (MHC‐I) and 1–6 (MHC‐II) amino acidic alleles per individual, with signs of positive selection. We obtained generalized additive mixed models to explore the associations between MHC‐I and MHC‐II diversity and latitude. We also explored the relationship between infection status and latitude/biome. We found a non‐linear association between the MHC‐II amino acidic allele diversity and latitude. Individuals from north Chile presented a lower MHC genetic diversity than those from other locations. We also found an association between deserts and xeric shrublands and a lower prevalence of Haemoproteus parasites. Our results support a lower MHC genetic in arid or semi‐arid habitats in the region with the lower prevalence of Haemoproteus parasites.